Study of variance analysis for a big project at CTRM Sdn Bhd / Nor Sharida Ab Sharif - Ab Sharif, Nor Sharida (Faculty of Business and Management, 2010)
The purposes of doing this research are to know what is variance analysis is all about. What are the types of variance analysis that the company applied and how they calculated on it. Also I want to identify what are the factors that can give effect to the results of variance analysis. There’s must be problem that occurred when analyze the variance, not only this company but also to other company. I want to identify what are the problems that arise in the analysis, the reason why they doing variance analysis, the implication if the analysis results to unfavorable variance and what are the action taken by them if this matter happened. The basic concept of variance analysis is difference between cost that was planned and actual level of cost achieved. From this research, I found that this company only focuses on material variance analysis rather than other types of variance analysis. They used the formula of (actual cost – estimated cost). There are many factors involved that reflect the results of variance analysis which are raw material used different from original material specification quoted, recent changes in purchase price of material and also employee efficiency in doing their job. The problems that arise when doing this analysis are probability that they might ignore the quality of the product in order to reduce cost of producing the product and the second problem is unfavorable price variance. When unfavorable price variance occurred, they will investigate why it was happened, normally it involved production line and also make revision to identify really quantity needed to produce the product. They have to take action because if not, it will decrease the profit of the company. Variance analysis is important because it provide a base against which actual performance can be measured and improve the business.